ANALISIS STRATEGI PELAYANAN PADA USAHA MIKRO DI PEKANBARU ( Studi Kasus Pada Usaha Bengkel Kecil ) - Lamin, Lamin (Eko dan Bisnis: Riau Economic and Business Review, 2016)
Based on the analysis of the research found that:  The results of partial testing on Tangible variables No significant impact on the Customer Satisfaction, Reliability significant impact on the Customer Satisfaction, Responsiveness no significant impact on the Customer Satisfaction , Assurance significant impact on the Customer Satisfaction,. Emphaty No significant impact on the Customer Satisfaction. With probability value (Sig.) = 0.000, because sig <0.05 then the result is Tangible, Reliability, Responsiveness, Assurance and Empathy jointly significant effect on customer satisfaction